STRATEGI KOMUNIKASI DIVISI KOORDINASI DAN KOMUNIKASI KEBIJAKAN BANK INDONESIA PROVINSI RIAU DALAM MENSOSIALISASIKAN PROGRAM BEASISWA - ", Vandimi; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Society's view of Bank Indonesia previously assess just focus on work related to the economy and monetary policy alone makes publicist Bank Indonesia made several strategies to inform the public that Bank Indonesia did not only focus on work related to the economy alone, but Bank Indonesia is also present in all aspects such as, education, tourism, social and cultural rights. Obviously this regard the Bank Indonesia needs to disseminate these programs to the community. One of their regular programs instituted a scholarship program, so that people know who worked on Bank Indonesia was not only related to one aspect only, but many aspects of one of them through the scholarship program of Bank Indonesia Riau Province.The purpose of this study was to determine the communication strategy and Communication Policy Coordination Division of Bank Indonesia Riau Province in disseminating scholarship program. This study used descriptive qualitative method. Technique determines the subject of research using purposive technique for informants inside and outside using a technique to informants accidental. Informants in this study is the manager of the division Coordination and Communication policy of Bank Indonesia Riau province, one person public relations staff of the division Coordination and Communication Policy of Bank Indonesia Riau province, two senior journalists of online media and print, one person academics or lecturers, and two students , Data collection techniques were interviews, observation, and documentation. Interactive data analysis techniques Miles and Huberman. To achieve the validity of the data in this study, the authors used an extension of participation and triangulation.Based on the research that has been done then the author obtained the results to identify the problems first result is a communicator strategy in disseminating scholarship program are employees of the division Coordination and Communication Policy of Bank Indonesia Riau Province. Strategy determination audiences are all special people of Riau province students in Riau and journalists linked to a transmitter of information. Communication message delivered in the form of an informative message is the medium used print media, electronic media, online media, and social media. Then associated with the identification of the latter is a response, in which the response associated with the strategy presented is a positive response from the public.